Cargoes of Iron Semi‐Products Recovered from Shipwrecks off the Carmel Coast, Israel. (21st January 2014) - Galili, E.; Bauvais, S.; Rosen, B.; Dillmann, P.
<x xml:space="preserve">Abstract</x> Underwater surveys along the Israeli Carmel coast have revealed six cargoes of iron semi‐products associated with shipwrecks. They are described and dated according to the associated artefacts. Metallographic and chemical analyses on samples from the biggest cargo have determined the stages of the chaîne opératoire, identified the properties of the iron and characterized the iron trade along the Israeli coast. The new discoveries contribute to our understanding of the circulation of iron in the South Levant, which was characterized by an almost complete absence of local iron production. During the Byzantine and Crusader periods, this absence was compensated by long‐distance sea trade, depending on political circumstances and restrictions. Three main types of iron semi‐products were identified: (a) partly consolidated blooms, (b) short pointed bars and (c) elongated pointed bars. The cargoes discovered represent a time period of nearly a millennium. Altogether, 148 iron semi‐products were studied. Of these, 166 were from cargo a, which was dated by coins to around 1130–1200 ce. Those coins could have been imported from Europe for Crusader military and civil uses in the Levant. The iron from cargoes b, d and f, dated perhaps to the Byzantine period, could have been imported from Anatolia or Venice for military and civil purposes.